Ethanol Conversion Into Acetone over Binary Cerium–zinc Oxide Catalysts - Tahmina Taghi; Vaghif Baghiyev (Chemical Engineering Transactions)
This paper is devoted to the study of ethanol conversion to acetone in the presence of water vapor using binary cerium-zinc oxide (Ce-Zn-O) catalysts. Catalysts containing ZnO have high selectivity in the reaction of ethanol conversion to acetone, while CeO2 has a high activity in ethanol conversion process. The catalytic activity of these samples was studied over a temperature range of 250–700°C. Chromatographic analysis was used to determine the products of the process and their yields. It was found that the atomic ratio of Ce to Zn significantly influences acetone yield and ethanol conversion. The highest yield of acetone made up 63.7 % and was observed on the sample with atomic ratio Ce:Zn = 2:8. Ethanol conversion on this sample achieved 87.7 %. X-ray diffraction analysis confirmed that all samples contained only the phases of the initial oxides: CeO2 and ZnO. Moreover, the degree of crystallinity of the prepared samples was studied. It was found that with increase in crystallinity the yield of the target product acetone and the overall ethanol conversion reduced. The obtained results prove the relationship between the structure and activity of Ce-Zn-O catalysts and offer both theoretical and practical importance of optimizing the process of obtaining of acetone from bioethanol. Instruct